2020
DOI: 10.21203/rs.3.rs-34427/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cluster randomised controlled feasibility study of HENRY: a community-based intervention aimed at reducing obesity rates in preschool children

Abstract: BackgroundCommunity based obesity prevention interventions are often commissioned despite the limited evidence base. HENRY (Health, Exercise, Nutrition for the Really Young) is a programme delivered to parents of preschool children across the UK. Early evidence suggests that it may be effective, but a robust evaluation has not been conducted. We initiated a systematic evaluation of HENRY by studying the feasibility of conducting a multi-centre definitive trial to evaluate its effectiveness and cost-effectivene… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…We used qualitative methods (interviews and focus groups) to explore contamination within the HENRY feasibility study [ 17 ] [Bryant et al, submitted at same time to Pilot and Feasibility Studies]. The feasibility study was an NIHR funded, multicentre, two-arm, cluster RCT.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We used qualitative methods (interviews and focus groups) to explore contamination within the HENRY feasibility study [ 17 ] [Bryant et al, submitted at same time to Pilot and Feasibility Studies]. The feasibility study was an NIHR funded, multicentre, two-arm, cluster RCT.…”
Section: Methodsmentioning
confidence: 99%
“…The feasibility study was an NIHR funded, multicentre, two-arm, cluster RCT. The protocol is reported elsewhere [ 17 ]. In brief, the study aimed to recruit 120 parents across 12 children’s centres in two local authorities (governments).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study methods have been reported in detail elsewhere [18] and are presented more brie y below. Following study commencement, three key protocol amendments were made: (1) Follow-up was reduced from 12 to 11 months due to an unexpected delay in the ethical approval process (approved by the Trial Steering Committee); (2) Additional consent was requested at follow-up to access HENRY programme attendance data; and (3) Telephone interviews were conducted with parents in the process evaluation to replace focus groups, which were not well attended.…”
Section: Designmentioning
confidence: 99%
“…Parents in the intervention arm attended the eight-week HENRY (Health, Exercise, Nutrition for the Really Young) programme delivered in children centre's to groups of 8-10 parents. Programme details are documented elsewhere [13,18,19]. In brief, it aims to provide parents with the skills and knowledge to support a healthy lifestyle in preschool children and their families.…”
Section: Interventionmentioning
confidence: 99%